2012
DOI: 10.4064/ap103-2-1
|View full text |Cite
|
Sign up to set email alerts
|

On isotropic Berwald metrics

Abstract: On isotropic Berwald metricsby Akbar Tayebi (Qom) and Behzad Najafi (Tehran)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…A. Tayebi and M. Rafie-Rad have showed that if F is an isotropic Berwald Finsler metric, then F is of isotropic S-curvature [20]. Tayebi-Najafi have proved that isotropic Berwald metrics of scalar flag curvature are of Randers type, [19]. In [14], Peyghan-Tayebi have proved that every generalized Berwald metrics with non-zero scalar flag curvature or isotropic Berwald curvature is a Randers metric.…”
Section: Introductionmentioning
confidence: 99%
“…A. Tayebi and M. Rafie-Rad have showed that if F is an isotropic Berwald Finsler metric, then F is of isotropic S-curvature [20]. Tayebi-Najafi have proved that isotropic Berwald metrics of scalar flag curvature are of Randers type, [19]. In [14], Peyghan-Tayebi have proved that every generalized Berwald metrics with non-zero scalar flag curvature or isotropic Berwald curvature is a Randers metric.…”
Section: Introductionmentioning
confidence: 99%
“…Tayebi-Rafie's result tells us that every isotropic Berwald metric is of isotropic S-curvature [8]. In [9], Tayebi-Najafi proved that isotropic Berwald metrics of scalar flag curvature are of Randers type. Recently, Guo-Liu-Mo have shown that every spherically symmetric Finsler metric of isotropic Berwald curvature is a Randers metric [4].…”
Section: Introductionmentioning
confidence: 99%
“…Tayebi-Rafie's result tells us that every isotropic Berwald metric is of isotropic S-curvature [16]. In [15], Tayebi-Najafi proved that isotropic Berwald metrics of scalar flag curvature are of Randers type. Recently, Guo-Liu-Mo have shown that every spherically symmetric Finsler metric of isotropic Berwald curvature is a Randers metric [10].…”
Section: Introductionmentioning
confidence: 99%